Muscle invasion in bladder cancer is associated with increased expression of ATG5, LC3A and CHOP - Maha Ali; Shimaa E. Soliman; Thoraya S. Eldeeb; Ebrahim aboeleuon; Shimaa H. Shaban; Dalia G. Mahran; M F. Abdelhafez; Shaimaa R. Ata; Hesham S. Ata; Eman Radwan (Molecular Biology Reports, 2026)

Licofelone-Loaded Poly(d,l-Lactide-Co-Glycolide) Nanoparticles to Enhance Therapeutic Action: A Novel Approach for the Topical Management of Irritant Contact Dermatitis - Khaled E. Abuelella; Shaimaa Mosallam; Amira A. El-Gazar; Ahmed Hassen Elshafeey; Sara M. Soliman (AAPS PharmSciTech, 2026)

Polycaprolactone Nanoparticles Boost Licofelone Transdermal Delivery for Osteoarthritis: In Vitro Characterization, Ex Vivo Permeability, and In Vivo Efficacy - Khaled E. Abuelella; Shaimaa Mosallam; Amira A. El-Gazar; Ahmed Hassen Elshafeey; Sara M. Soliman (Journal of Pharmaceutical Innovation, 2026)
Purpose Polycaprolactone nanoparticles (PCLNPs) are biodegradable carriers widely investigated for drug delivery applications. Their hydrophobic nature and high encapsulation efficiency make them ideal for sustained drug release. This study aimed to encapsulate licofelone (LF), a dual COX/5-LOX inhibitor, within PCLNPs to enhance its therapeutic efficacy for osteoarthritis treatment through transdermal administration. Methods LF loaded PCLNPs were formulated using the nanoprecipitation method. A 2 3 full factorial design was employed by varying PCL (100 or 150 mg), PVA (150 or 300 mg), and SDC (10 or 20 mg) at two levels each. The optimum formula was F8, consisting of 150 mg PCL, 300 mg PVA, and 20 mg SDC. Results F8 formulation exhibited a spherical shape with a particle size (PS) of 269.3 ± 1.90 nm, an encapsulation efficiency (EE%) of 89 ± 0.56%, a polydispersity index (PDI) of 0.21 ± 0.02, and a zeta potential (ZP) of -27.85 ± 0.07 mV. The F8 gel exhibited a sustained-release profile, with drug permeation across excised rat skin 2.47-fold higher than that of the LF gel ( n = 3, p < 0.05). In vivo evaluation revealed significant chondroprotective and regenerative effects in a monoiodoacetate (MIA)-induced osteoarthritis rat model. F8 gel suppressed the release of inflammatory and pain mediators (5-LOX, COX, LTB 4 , and PGE2) and serum cartilage degradation products (CTX-II and COMP) after 10 days of treatment. Histological evaluation further confirmed its ability to prevent cartilage surface depletion and matrix loss. Conclusion The optimized F8 gel achieved sustained LF release for approximately 20 h, enhanced ex vivo permeation by 2.47-fold relative to LF gel, and significantly reduced inflammatory mediators and cartilage degradation markers in vivo, highlighting its potential as a promising transdermal therapy for osteoarthritis management. Graphical Abstract

Association of cell-free DNA, micro-RNA 21, and micro-RNA 146a levels with rheumatoid arthritis activity - Hend Moness; Reham Ali Ibrahim; Samar A. Soliman; Al-Shaimaa M. Abdel-Naiem; Shaimaa Moustafa Hafez; Noha M. Abdullah (Molecular Biology Reports, 2025)

Selenium and vitamin E supplementation alleviate high-fat diet-induced stress in oreochromis niloticus: enhancing growth, antioxidant defense, and disease resistance - Nagwa I. S. Abu-Zahra; Shaimaa Elbaz; Ghada A. El-Gammal; Amina S. Kassab; Mofeed Gouda; Mohamed M. Elseify; Shireen Soliman (Aquaculture International, 2025)
This study investigated the interactive effects of dietary fat levels and selenium–vitamin E (Se + VE) supplementation on the growth performance, antioxidant status, immune response, and disease resistance of Oreochromis niloticus . The fish were fed diets containing 5%, 10%, or 15% lipids with or without Se + VE supplementation over a 60-day experimental period. Growth metrics, including final weight, weight gain, average daily gain, and feed efficiency, were significantly improved in the group receiving 10% fat supplemented with Se + VE, whereas high-fat (15%) diets without supplementation resulted in impaired performance ( P P P Streptococcus agalactiae , Kaplan–Meier survival analysis revealed significantly improved survival rates in the Se + VE-supplemented groups, with the greatest protection observed in the 5% and 10% fat diet groups. The clinical and pathological scores corroborated these findings, revealing reduced lesion severity in the supplemented groups. Collectively, these results demonstrate that dietary supplementation with Se and VE effectively counters the adverse effects of high-fat diets, improving metabolic balance, tissue integrity, and disease resistance in O. niloticus .

Nigella sativa and carvacrol supplementation modulates physiological, immune, and disease resistance responses in Oreochromis niloticus: evidence of interaction in selected parameters - Nagwa I. S. Abu-Zahra; Shireen Soliman; Amany M. Ghoniem; Shaimaa Elbaz (Aquaculture International, 2025)
Intensified aquaculture practices have increased the vulnerability of farmed fish to infectious pathogens, highlighting nutritional strategies to increase health and reduce antibiotic reliance. Dietary antioxidants such as Nigella sativa (NI) and carvacrol (CA) have shown potential as functional feed additives because of their synergistic effects under bacterial challenge. This study evaluated whether dietary supplementation with NI aqueous extract, CA, or their combination could enhance growth, antioxidant defense, immune function, and disease resistance in Oreochromis niloticus challenged with Aeromonas hydrophila . A total of 120 fish (mean weight 32.28 ± 0.32 g) were randomly assigned to four groups with three replicates per group ( n = 30 fish/group, 10 fish/replicate): control, NI (10 g/kg diet), CA (1 g/kg diet), and NI + CA. Fish were fed for eight weeks, followed by experimental infection with A. hydrophila . Growth performance, hematological and biochemical indices, antioxidant enzymes (SOD, GST), lipid peroxidation (MDA), immune parameters (phagocytic activity, myeloperoxidase, total immunoglobulin), and bacterial re-isolation were assessed. Dietary inclusion of NI, CA, or NI + CA significantly improved growth parameters, with the combined group showing the greatest final body weight, weight gain, and specific growth rate, along with a reduced feed conversion ratio. Hematological and biochemical analyses revealed enhanced hemoglobin and leukocyte profiles and favorable modulation of protein, lipid, and glucose metabolism. Supplementation elevated antioxidant enzymes and reduced lipid peroxidation, indicating improved redox balance. Immune assays revealed increased phagocytic activity, myeloperoxidase response, and total immunoglobulin. Following A. hydrophila challenge, the NI + CA group displayed reduced clinical signs, milder lesions, a lower bacterial load, and the highest relative percent survival. Co-supplementation with NI and CA exerted synergistic protective effects across multiple physiological systems, increasing the antioxidant capacity, immune competence, and resistance to bacterial infection in O. niloticus . This study is among the first to demonstrate the synergistic benefits of NI and CA against bacterial challenge in O. niloticus , supporting their application as natural, cost-effective immunostimulants in functional aquafeeds.

Retraction Note: Do Zinc Supplements Enhance the Clinical Efficacy of Hydroxychloroquine?: A Randomized, Multicenter Trial - Sherief Abd-Elsalam; Shaimaa Soliman; Eslam Saber Esmail; Mai Khalaf; Ehab F. Mostafa; Mohammed A. Medhat; Ossama Ashraf Ahmed; Mohamed Samir Abd El Ghafar; Mohamed Alboraie; Sahar M. Hassany (Biological Trace Element Research, 2025)

Possible beneficial effects of nano chitosan against doxycycline toxicity in Nile tilapia (Oreochromis niloticus) - Mahmoud S. Sabra; Mohamed Abd El-Aal; Shaimaa K.A. Idriss; Hamdy A.M. Soliman; Sally M. Salaah; Alaa El-Din H. Sayed (Aquaculture, 2024)

Anti-nemic potential of Laurencia papillosa and Dilophys fasciola biosynthesized nano-extracts against tomato root-knot nematode Meloidogyne incognita - Gaziea M. Soliman; Shaimaa A. Nour; Ayman A. Mohammad; Sameh M. El‑Sawy; Soha A. Murad; Dalia A. Youssef; Wafaa M. A. El-Nagdi; Eman A. Ibrahim (Phytoparasitica, 2024)
Due to the damaging effects of root-knot nematodes on crops and the dangerous effects of chemical nematicides on both people and the environment in Egypt, the purpose of this study was to assess the power of polysaccharides and polyphenol extracts as well as their nano-forms from marine algae ( Laurencia papillosa and Dilophys fasciola ) used as eco-friendly alternatives for the control of Meloidogyne incognita . The nano-forms of algal extracts efficiently suppressed M. incognita egg hatching and increased juvenile mortality compared to the control. The tested treatments effectively decreased galls and egg masses of tomato roots compared to the control in the field. Dilophys fasciola extract and its nano-form showed promising nematicidal activity compared to L. papillosa extract. Generally, algal treatments boosted tomato plant defense system against M. incognita by triggering the production of some biochemical constituents such as phenolic compounds, polyphenol oxidase and chitinase enzymes. Consequently, the productivity and quality parameters of tomato fruits significantly increased.

Oxidative Stress and Immunopathological Alterations of Clarias gariepinus Exposed to Monocyclic Aromatic Hydrocarbons (BTX) - Alaa El-Din H. Sayed; Hamdy A. M. Soliman; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Water, Air, & Soil Pollution, 2023)
This study’s goal was to assess the catfish’s response to exposure to monoaromatic petroleum hydrocarbons (benzene, toluene, and xylene) and its recovery after exposure using oxidative stress, histopathological, and immunological changes as biomarkers. Four groups: one as control and other three exposed to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L), respectively, for 30 days and then recovery period for 30 days. The levels of the cortisol, lipid peroxidation, and cytokines (IL-1β, IL-6) increased significantly ( p < 0.05) after exposure to benzene and xylene compared to control. Superoxide dismutase (SOD), total antioxidant capacity (TAC), and acetylcholinstease (Ach) decreased significantly ( p < 0.05) in fishes exposed to benzene only compared to control group. While glutathione-S-transferase (GST) did not show any change in different treatment groups compared to control group. The histopathological signs of liver exposed to benzene, toluene, and xylene displayed aggregation of melanomacrophages, congestion of sinusoids, vacuolar degeneration of hepatocytes, necrotic area with inflammatory cell infiltration, and thrombus of central vein. Kidney exposed to benzene, toluene, and xylene showed dilatation of Bowman’s space with atrophy of glomerular tuft, lyses of RBCs with mononuclear cell infiltration, multifocal area of hemopoietic tissue necrosis, organized thrombus with perivascular hemorrhage, focal inflammatory cellular reaction, renal tubular necrosis, and thrombus of blood vessels. Spleen exposed to benzene, toluene, and xylene showed hyperplasia of lymphoid follicles in white pulp in a mild degree. These lesions appeared to a mild degree or disappeared completely after recovery period to BTX except spleen. In conclusion, monocyclic aromatic hydrocarbons (BTX) are hazardous to fish and the toxicity level was as benzene > xylene > toluene even though after recovery period.

Lipoxin A4 attenuated dexamethasone-induced muscle atrophy via activation of PGC-1α/Nrf2/TFAM pathway - Fatma H. Rizk; Nema A. Soliman; Shaimaa M. Kashef; Amira A. Elsaadany (Journal of Physiology and Biochemistry, 2023)
Prolonged dexamethasone (DEX) administration causes skeletal muscle atrophy through induction of both oxidative stress and mitochondrial dysfunction. Lipoxin A4 (LXA4) is a recognized antioxidant but its effect against DEX-induced muscle atrophy has not been studied yet. This study aimed to assess the potential ameliorating effect of LXA4 on DEX-induced muscle atrophy and investigate the possible involvement of the mitochondrial dynamics pathway and the redox state in this effect. Forty male rats were divided into four groups; normal control, LXA4-treated, DEX-treated, and LXA4 plus DEX-treated. At the end of the experiment, LXA4 counteracted the effect of DEX on different parameters including muscle weight, muscle strength, serum creatine kinase activity, malondialdehyde and protein carbonyl contents, Na/K-ATPase and citrate synthase activities, mitochondrial transmembrane potential, mitochondrial transcription factor (TFAM), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), and nuclear factor erythroid 2-related factor 2 (Nrf2). These findings signify the promising therapeutic effect of LXA4 against DEX-induced skeletal muscle atrophy and indicate the possible involvement of LXA4-induced mitochondrial activation in addition to its well-known antioxidant effects.

Retraction Note to: Efficacy and safety of sofosbuvir plus ribavirin for treatment of cirrhotic patients with genotype 4 hepatitis C virus in real-life clinical practice - Sherief Abd-Elsalam; Mohamed Sharaf-Eldin; Shaimaa Soliman; Asem Elfert; Rehab Badawi; Youssef K. Ahmad (Archives of Virology, 2022)

Variation among individuals of Citrullus colocynthis from a desert population in morphological, genetic, and germination attributes - Shaimaa Al-Nablsi; Ali El-Keblawy; Kareem A. Mosa; Sameh Soliman (Tropical Ecology, 2022)

Molecular characterization of alpha subunit 1 of sodium pump (ATP1A1) gene in Camelus dromedarius: its differential tissue expression potentially interprets the role in osmoregulation - A. H. El kasas; I. M. Farag; H. R. Darwish; Y. A. Soliman; E. M. El Nagar; Marwa A. Ibrahim; Shaimaa Kamel; Mohamad Warda (Molecular Biology Reports, 2022)

Retraction Note to: Efficacy of favipiravir in COVID‑19 treatment: a multi‑center randomized study - Hany M. Dabbous; Sherief Abd‑Elsalam; Manal H. El‑Sayed; Ahmed F. Sherief; Fatma F. S. Ebeid; Mohamed Samir Abd El Ghafar; Shaimaa Soliman; Mohamed Elbahnasawy; Rehab Badawi; Mohamed Awad Tageldin (Archives of Virology, 2022)

Effects of remote virtual work environment during COVID-19 pandemic on technostress among Menoufia University Staff, Egypt: a cross-sectional study - Hala Marawan Gabr; Shaimaa Sherif Soliman; Heba Khodary Allam; Shaimaa Yaihya Abdel Raouf (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Do Zinc Supplements Enhance the Clinical Efficacy of Hydroxychloroquine?: a Randomized, Multicenter Trial - Sherief Abd-Elsalam; Shaimaa Soliman; Eslam Saber Esmail; Mai Khalaf; Ehab F. Mostafa; Mohammed A. Medhat; Ossama Ashraf Ahmed; Mohamed Samir Abd El Ghafar; Mohamed Alboraie; Sahar M. Hassany (Biological Trace Element Research, 2021)

RETRACTED ARTICLE: Efficacy of favipiravir in COVID-19 treatment: a multi-center randomized study - Hany M. Dabbous; Sherief Abd-Elsalam; Manal H. El-Sayed; Ahmed F. Sherief; Fatma F. S. Ebeid; Mohamed Samir Abd El Ghafar; Shaimaa Soliman; Mohamed Elbahnasawy; Rehab Badawi; Mohamed Awad Tageldin (Archives of Virology, 2021)

Correction to: MicroRNA signature in hepatocellular carcinoma patients: identification of potential markers - Mohammed Elhendawy; Enas A. Abdul-Baki; Sherief Abd-Elsalam; Maha M. Hagras; Abdul-Aziz Zidan; Amira Y. Abdel-Naby; Mona Watany; Ibrahem Ali Elkabash; Mohamed Labib Salem; Mohamed Elshanshoury; Shaimaa Soliman; Said Abdou (Molecular Biology Reports, 2020)

MicroRNA signature in hepatocellular carcinoma patients: identification of potential markers - Mohammed Elhendawy; Enas A. Abdul-Baki; Sherief Abd-Elsalam; Maha M. Hagras; Abdul-Aziz Zidan; Amira Y. Abdel-Naby; Mona Watny; Ibrahem Ali Elkabash; Mohamed Labib Salem; Mohamed Elshanshoury; Shaimaa Soliman; Said Abdou (Molecular Biology Reports, 2020)

RETRACTED ARTICLE: Efficacy and safety of sofosbuvir plus ribavirin for treatment of cirrhotic patients with genotype 4 hepatitis C virus in real-life clinical practice - Sherief Abd-Elsalam; Mohamed Sharaf-Eldin; Shaimaa Soliman; Asem Elfert; Rehab Badawi; Youssef K. Ahmad (Archives of Virology, 2018)

Aicardi-Goutières syndrome: unusual neuro-radiological manifestations - Ghada M. H. Abdel-Salam; Mohamed S. Abdel-Hamid; Shaimaa A. Mohammad; Sherif F. Abdel-Ghafar; Doaa R. Soliman; Hala T. EL-Bassyouni; Laila Effat; Maha S. Zaki (Metabolic Brain Disease, 2017)

Musca domestica laboratory susceptibility to three ethnobotanical culinary plants - Elham A. El Zayyat; Mohammed I. Soliman; Noha A. Elleboudy; Shaimaa E. Ofaa (Environmental Science and Pollution Research, 2015)